Extending working lives: the case of Denmark - Barslund, Mikkel (Brussels, 2015)
"Extending working lives has been a key item on the political agenda in Denmark for at least two decades now. This study details recent and prospective reforms to the voluntary early retirement scheme and the pension age, as well as current policy initiatives to keep older workers in employment. Other aspects central to a long working life, such as health, lifelong learning, age management practices in companies, and elderly workers’ motivation are discussed in depth. Overall, Denmark is in a relatively good state when it comes to older workers’ labour market participation and related job satisfaction. This impacts positively on the public finance challenge linked to population ageing which, given agreed reforms, should be manageable. Ongoing reform implementation is likely to substantially increase the employment of those aged 60 and over. Nevertheless, surveys point to age discrimination as a potential problem and people who fall into unemployment at a late stage of their careers still face challenges to reemployment."